Merger and Acquisition Analysis in Creating Value for Shareholders in The Infrastructure and Utility Sector - Valentina Hemas Widianova; Permata Wulandari (Journal of International Conference Proceedings (JICP), 2021)
Trough 20 – years period their merger and acquisition (M&A) in sector infrastructure and utilities are the pledge of the most country in the world, especially in Asia with most emerging countries. This study aims to know the relation about M&A activities to value shareholders in infrastructure and utilities sector in during last 20 years and year of crisis in 2020. Observe for acquire and target companies using event study approach to find Cumulative Average Abnormal Return (CAAR) on M&A activities that represent the value for the shareholders. Set event window for 31 days, consist of 15 days before the announcement and 15 days after announcement. Using sample of listed companies who making acquisition activities in Asia which size of the deal above USD 30 million. The result shows that the acquirers give positive CAAR that statistically significant 10% and the targets give positive CAAR statistically significant 5 %. The target company has higher cumulative abnormal average return than the acquirer company. Then M&A activity during crisis shows that for acquirer give positive not significant CAAR with 4,6% abnormal return and target give positive CAAR 3.4% but not significant. The target gives higher CAAR positive for t-15 to t+7 than the acquirer.